Secondary battery

By modifying the surface of lithium-containing composite oxides with B, P, and Si in secondary batteries using sulfide solid electrolytes, the initial capacity and cycle durability are enhanced, overcoming the performance limitations of existing technologies.

JP7611261B2Active Publication Date: 2025-01-09NISSAN MOTOR CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022553223
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-01
Publication Date
2025-01-09
Estimated Expiration
2040-10-01

AI Technical Summary

Technical Problem

Secondary batteries using sulfide solid electrolytes with sulfur and phosphorus and high nickel positive electrode active materials face challenges in achieving sufficient initial capacity and cycle durability.

Method used

A positive electrode active material made of a lithium-containing composite oxide with specific chemical composition and surface modification by introducing additive elements such as B, P, and Si in high molar concentrations within a 100 nm surface layer, combined with a sulfide solid electrolyte, enhances the battery's performance.

Benefits of technology

The solution significantly improves the initial capacity and cycle durability of secondary batteries, addressing the limitations of conventional technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611261000002
    Figure 0007611261000002
  • Figure 0007611261000003
    Figure 0007611261000003
  • Figure 0007611261000004
    Figure 0007611261000004
Patent Text Reader

Abstract

[Problem] To provide a means by which it is possible to sufficiently improve the initial capacity and cycle durability of a secondary battery in which is used a high-nickel-based positive electrode active material and a sulfide solid electrolyte containing sulfur and phosphorus. [Solution] A secondary battery comprising a power generation element obtained by laminating, in this order: a positive electrode which includes a positive electrode active material layer containing the positive electrode active material that comprises a so-called high-nickel-based lithium-containing composite oxide; a solid electrolyte layer which contains a sulfide solid electrolyte containing sulfur and phosphorous; and a negative electrode which includes a negative electrode active material layer containing a negative electrode active material, wherein one or more additive elements selected from the group consisting of B, P, S, and Si are caused to be present in a higher molar concentration than Ni in a surface layer region having a depth of 100 nm or less from the surface of particles of the lithium-containing composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium-ion secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium-ion secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.

[0004] Currently, lithium-ion secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and for these liquid-based lithium-ion secondary batteries, stricter safety measures against leakage, short circuits, overcharging, etc. are required than for other batteries.

[0005] In recent years, therefore, research and development of all-solid-state batteries, such as all-solid-state lithium-ion secondary batteries that use oxide- or sulfide-based solid electrolytes, has been actively conducted. A solid electrolyte is a material that is mainly composed of an ion conductor that can conduct ions in a solid state. Therefore, in principle, all-solid-state lithium-ion secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium-ion secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery.

[0006] However, in an all-solid-state lithium-ion secondary battery using a sulfide solid electrolyte in combination with a positive electrode active material made of a metal oxide, problems such as an increase in battery resistance and a decrease in output characteristics of the all-solid-state battery may occur due to the low electronic conductivity of the metal oxide. In addition, when a conductive material is added to deal with such problems, the content of the positive electrode active material is relatively decreased, resulting in a problem of a decrease in the energy density of the battery.

[0007] For the purpose of preventing the occurrence of such problems, for example, Patent Document 1 discloses a technology in which a reaction suppression layer containing carbonaceous material and a lithium-containing oxide such as LiNbO3 is formed on the surface of a positive electrode active material to form a composite positive electrode active material, thereby preventing a decrease in the battery resistance of an all-solid-state battery and improving the output characteristics. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2013 / 022034 Brochure Summary of the Invention [Problem to be solved by the invention]

[0009] The present inventors have investigated the use of a high-nickel-based positive electrode active material, which is a high-capacity positive electrode active material, in a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus as an electrolyte layer. As a result, it was found that sufficient performance could not be obtained in terms of initial capacity and cycle durability. Therefore, the present inventors have attempted to improve these performances by utilizing the technology described in the above-mentioned Patent Document 1.

[0010] However, even with the technique disclosed in Patent Document 1, it was not possible to sufficiently improve the initial capacity and cycle durability of a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus and a high-nickel positive electrode active material.

[0011] Therefore, an object of the present invention is to provide a means for sufficiently improving the initial capacity and cycle durability of a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus and a high-nickel positive electrode active material. [Means for solving the problem]

[0012] The present inventors have conducted extensive research with the aim of solving the above problems. As a result, they have found that the above problems can be solved by introducing a predetermined element into a surface layer region of a particle of a lithium-containing composite oxide having a predetermined central composition in a positive electrode active material made of the lithium-containing composite oxide and combining this with a sulfide solid electrolyte containing sulfur and phosphorus, and have completed the present invention.

[0013] That is, according to one embodiment of the present invention, the composition of the central portion is represented by the following chemical formula (1): Li 1+q Ni x Co y Mn z M p O2(1) In the formula, -0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. the positive electrode including a positive electrode active material layer containing a positive electrode active material made of a lithium-containing composite oxide represented by the formula: Effect of the Invention

[0014] According to the present invention, it is possible to sufficiently improve the initial capacity and cycle durability of a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus and a high-nickel positive electrode active material. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium ion secondary battery, which is one embodiment of the lithium ion secondary battery according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a bipolar type all-solid-state lithium ion secondary battery, which is one embodiment of the lithium ion secondary battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 《Secondary battery》 In one embodiment of the present invention, the composition of the core portion is represented by the following chemical formula (1): Li 1+q Ni x Co y Mn z M p O2(1) In the formula, -0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. a solid electrolyte layer containing a sulfide solid electrolyte containing sulfur and phosphorus, and a negative electrode containing a negative electrode active material, laminated in this order, and one or more additive elements selected from the group consisting of B, P, S and Si are present in a molar concentration higher than that of Ni in a surface layer region within a depth of 100 nm from the surface of a particle of the lithium-containing composite oxide.

[0017] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation, and may differ from the actual ratios.

[0018] FIG. 1 is a perspective view showing the appearance of a flat-laminated all-solid-state lithium-ion secondary battery, which is one embodiment of the lithium-ion secondary battery according to the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat-laminated non-bipolar lithium-ion secondary battery shown in FIG. 1 and FIG. 2 (hereinafter, also simply referred to as a "laminated battery") will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the lithium-ion secondary battery according to this embodiment, it can be applied to both non-bipolar (internal parallel connection type) batteries and bipolar (internal series connection type) batteries.

[0019] 1, the stacked battery 10a has a flat rectangular shape, with a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed with the negative electrode current collector 25 and the positive electrode current collector 27 extending to the outside.

[0020] The lithium ion secondary battery according to the present embodiment is not limited to a laminated flat shape. A wound lithium ion secondary battery may be cylindrical, or may be a rectangular flat shape obtained by deforming such a cylindrical shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.

[0021] There is also no particular limitation on the removal of the current collectors (25, 27) shown in Fig. 1. The negative current collector 25 and the positive current collector 27 may be pulled out from the same side, or the negative current collector 25 and the positive current collector 27 may each be divided into a plurality of pieces and removed from each side, and are not limited to what is shown in Fig. 1. In addition, in a wound type lithium ion battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.

[0022] 2, the stacked battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material are disposed on both sides of a positive electrode collector 11". The negative electrode has a structure in which negative electrode active material layers 13 containing a negative electrode active material are disposed on both sides of a negative electrode collector 11'. Specifically, the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order such that one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 1 has a structure in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0023] As shown in FIG. 2, the outermost positive electrode current collectors located on both outermost layers of the power generating element 21 each have a positive electrode active material layer 15 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector. In some cases, the negative electrode active material layer 13 and the positive electrode active material layer 15 may be used as the negative electrode and positive electrode, respectively, without using the current collectors (11', 11")

[0024] Negative current collector 11′ and positive current collector 11″ are respectively attached with negative current collector plate (tab) 25 and positive current collector plate (tab) 27 that are electrically connected to the respective electrodes (positive and negative electrodes), and have a structure in which they are sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 27 and negative current collector 25 may be attached to positive current collector 11″ and negative current collector 11′ of each electrode by ultrasonic welding, resistance welding, or the like, respectively, via positive electrode leads and negative electrode leads (not shown) as necessary.

[0025] The main components of the lithium ion secondary battery according to this embodiment will be described below.

[0026] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.

[0027] Specifically, the metal may be aluminum, nickel, iron, stainless steel, titanium, copper, etc. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, etc. may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, adhesion of the negative electrode active material by sputtering to the current collector, etc.

[0028] The latter conductive resin may be a resin obtained by adding a conductive filler to a non-conductive polymeric material as required.

[0029] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.

[0030] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.

[0031] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, and Sb, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.

[0032] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally 5 to 80 mass % relative to the total mass of the current collector (100 mass %).

[0033] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the negative electrode active material layer and the positive electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the negative electrode active material layer described later constitutes the negative electrode as it is, and the positive electrode active material layer described later constitutes the positive electrode as it is.

[0034] [Negative electrode (negative electrode active material layer)] In the secondary battery according to this embodiment, the negative electrode active material layer 13 contains a negative electrode active material. The type of the negative electrode active material is not particularly limited, but may include a carbon material, a metal oxide, and a metal active material. Examples of the carbon material include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the metal oxide include Nb2O5, Li4Ti5O 12 and the like. Furthermore, silicon-based negative electrode active materials and tin-based negative electrode active materials may be used. Here, silicon and tin belong to the 14th group of elements, and are known to be negative electrode active materials that can greatly improve the capacity of non-aqueous electrolyte secondary batteries. These simple substances can absorb and release a large number of charge carriers (lithium ions, etc.) per unit volume (mass), and therefore become high-capacity negative electrode active materials. Here, it is preferable to use Si simple substance as the silicon-based negative electrode active material. Similarly, SiO 2 disproportionated into two phases, a Si phase and a silicon oxide phase, is also used. xIt is also preferable to use silicon oxides such as (0.3≦x≦1.6). In this case, the range of x is more preferably 0.5≦x≦1.5, and even more preferably 0.7≦x≦1.2. Furthermore, an alloy containing silicon (silicon-containing alloy-based negative electrode active material) may be used. On the other hand, examples of negative electrode active materials containing tin element (tin-based negative electrode active materials) include simple Sn, tin alloys (Cu-Sn alloys, Co-Sn alloys), amorphous tin oxides, tin silicon oxides, and the like. Among these, examples of amorphous tin oxides include SnB 0.4 P 0.6 O 3.1 Examples of the tin silicon oxide include SnSiO3. Metals containing lithium may be used as the negative electrode active material. Such negative electrode active materials are not particularly limited as long as they are active materials containing lithium, and examples thereof include metallic lithium and lithium-containing alloys. Examples of the lithium-containing alloys include alloys of Li and at least one of In, Al, Si, and Sn. In some cases, two or more negative electrode active materials may be used in combination. Of course, negative electrode active materials other than the above may be used. The negative electrode active material preferably contains metallic lithium, a silicon-based negative electrode active material, or a tin-based negative electrode active material, and particularly preferably contains metallic lithium.

[0035] The shape of the negative electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the negative electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.

[0036] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.

[0037] The negative electrode active material layer preferably further includes a solid electrolyte. By including the solid electrolyte in the negative electrode active material layer, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and the sulfide solid electrolyte is preferable.

[0038] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, and LiI-LiBr-Li3PS 4、 Li3PS 4、 Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2 S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0039] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4 and LiI-LiBr-Li3PS 4、Examples include Li3PS4. As sulfide solid electrolytes having a Li4P2S7 skeleton, for example, Li-P-S-based solid electrolytes called LPS (e.g., Li7P3S 11 ) can be mentioned. As sulfide solid electrolytes, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing P element, and the sulfide solid electrolyte is more preferably a material mainly composed of Li2S - P2S5. Furthermore, the sulfide solid electrolyte may contain halogen (F, Cl, Br, I).

[0040] When the sulfide solid electrolyte is of the Li2S - P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in terms of molar ratio, and among them, Li2S:P2S5 = 70:30 to 80:20 is more preferable.

[0041] The sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid-phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as ball milling) on the raw material composition. The crystallized sulfide glass can be obtained, for example, by heat-treating the sulfide glass at a temperature above the crystallization temperature. The ionic conductivity (e.g., Li ion conductivity) of the sulfide solid electrolyte at room temperature (25 °C) is preferably, for example, 1×10 -5 S / cm or more, and more preferably 1×10 -4 S / cm or more. The value of the ionic conductivity of the solid electrolyte can be measured by the AC impedance method.

[0042] Examples of the oxide solid electrolyte include compounds having a NASICON-type structure. As an example of a compound having a NASICON-type structure, the general formula Li 1+x Alx Ge 2-x Compounds represented by the formula (PO4)3 (0≦x≦2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0043] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.

[0044] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.

[0045] The negative electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.

[0046] Examples of the conductive assistant include metals such as aluminum, stainless steel (SUS), silver, gold, copper, and titanium, alloys or metal oxides containing these metals; carbon fibers (specifically, vapor-grown carbon fibers (VGCF), polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, rayon-based carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), and carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), but are not limited thereto. In addition, a particulate ceramic material or a resin material coated with the above-mentioned metal material by plating or the like can also be used as a conductive assistant. Among these conductive assistants, from the viewpoint of electrical stability, it is preferable to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbon, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbon, and even more preferably to include at least one carbon. These conductive assistants may be used alone or in combination of two or more.

[0047] The conductive assistant is preferably in the form of particles or fibers. When the conductive assistant is in the form of particles, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, etc.

[0048] When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical properties of the battery. In this specification, the "particle diameter of the conductive assistant" means the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle diameter of the conductive assistant" is calculated as the average value of particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0049] When the negative electrode active material layer contains a conductive assistant, the content of the conductive assistant in the negative electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the negative electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the negative electrode active material layer, which can effectively contribute to improving the battery characteristics.

[0050] On the other hand, the binder is not particularly limited, but examples thereof include the following materials:

[0051] Thermoplastic polymers such as polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated derivatives, styrene-isoprene-styrene block copolymer and its hydrogenated derivatives, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene Examples of such fluororesins include ethylene-chlorotrifluoroethylene copolymer (ECTFE) and polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), and vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber), as well as epoxy resins. Among these, polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are more preferable.

[0052] The thickness of the negative electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0053] [Solid electrolyte layer] In the secondary battery according to this embodiment, the solid electrolyte layer is interposed between the above-mentioned positive electrode active material layer and negative electrode active material layer, and is a layer that essentially contains a sulfide solid electrolyte that contains sulfur and phosphorus.

[0054] There is no particular restriction on the specific form of the sulfide solid electrolyte contained in the solid electrolyte layer, and the phosphorus-containing sulfide solid electrolytes exemplified in the section on the negative electrode active material layer can be used in the same manner. Specifically, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS 4、 Li3PS 4、 Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-SiS2-Li3PO4, LiI-Li3PS4, LiI-LiBr-Li3PS 4、 Li3PS4, LPS (Li-PS solid electrolyte (e.g., Li7P3S 11 )), LGPS(Li (4-x) Ge (1-x) P xExamples include S4 (where 0 < x < 1 is satisfied). Among them, the sulfide solid electrolyte contained in the solid electrolyte layer is more preferably a material mainly composed of Li2S-P2S5. In some cases, a solid electrolyte other than the above-described sulfide solid electrolyte containing phosphorus may be used in combination. However, the proportion of the content of the predetermined sulfide solid electrolyte in the total amount of the solid electrolyte of 100% by mass is preferably 50% by mass or more, more preferably 70% by mass or more, still more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0055] In addition to the above-described predetermined sulfide solid electrolyte, the solid electrolyte layer may further contain a binder. For the binder that can be contained in the solid electrolyte layer, the examples and preferred forms described in the column of the negative electrode active material layer can be similarly adopted.

[0056] The thickness of the solid electrolyte layer varies depending on the configuration of the target lithium ion secondary battery. From the viewpoint of improving the volume energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and still more preferably 400 μm or less. On the other hand, there is no particular limitation on the lower limit value of the thickness of the solid electrolyte layer, but it is preferably 10 μm or more, more preferably 50 μm or more, and still more preferably 100 μm or more.

[0057] [Positive Electrode Active Material Layer] In the secondary battery according to this embodiment, the positive electrode active material layer contains a so-called high-nickel positive electrode active material. Specifically, the positive electrode active material contained in the positive electrode active material layer of the secondary battery according to this embodiment has a composition in the central part represented by the following chemical formula (1): Li 1+q Ni x Co y Mn z M p O2(1) In the formula, -0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. The lithium-containing composite oxide is represented by the formula:

[0058] In the general formula (1), q is -0.02≦q≦0.20. From the viewpoint of increasing the initial discharge capacity, q is preferably 0≦q≦0.10. In addition, in the general formula (1), x is 0.50≦x≦1.0. From the viewpoint of increasing the initial discharge capacity, x is preferably 0.50≦x<1.0, more preferably 0.55≦x≦0.95, even more preferably 0.60≦x≦0.90, and particularly preferably 0.70≦x≦0.85. In addition, y and z in the general formula (1) are 0≦(y,z)≦0.50. From the viewpoint of excellent safety, it is preferably 0<(y,z)≦0.50, more preferably 0.05≦(y,z)≦0.45, and even more preferably 0.10≦(y,z)≦0.40. x / z is preferably greater than 1, more preferably 1.2 or greater, and further preferably 1.5 to 99.

[0059] One of the features of the positive electrode active material according to this embodiment is that the composition of the surface region of the lithium-containing composite oxide particles constituting the positive electrode active material is different from the composition of the central portion represented by the above-mentioned general formula (1). Specifically, in the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles having the above-mentioned composition of the central portion (general formula (1)), one or more additive elements selected from the group consisting of B, P, S and Si are present at a molar concentration higher than that of Ni. In other words, in the above-mentioned surface region, in addition to the Ni element, at least one element of B, P, S and Si coexists at a molar concentration higher than that of Ni element. Note that in the present invention, it is necessary that there are one or more additive elements "present at a molar concentration higher than that of Ni element in the surface region". Therefore, when the molar concentration of any additive element in the surface region is equal to or lower than that of Ni element, it is not included in the scope of the present invention even if the total molar concentration of the multiple additive elements is higher than that of Ni element.

[0060] The elemental composition of the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particle can be analyzed by X-ray photoelectron spectroscopy (XPS). The composition of the central part of the lithium-containing composite oxide can also be analyzed by XPS. When performing XPS measurement, a charge correction is performed to shift the C1s peak top to 284.6 [eV].

[0061] There is no particular restriction on the concentration (abundance) of the additive element in the surface region, but the concentration of the additive element is preferably 1 to 30 mol%, more preferably 17 to 30 mol%, as a molar percentage relative to all elements in the surface region. Here, the concentration of the additive element when a plurality of additive elements are present in the surface region is the total concentration of the plurality of additive elements. There is also no particular restriction on the profile of the concentration change of the additive element in the depth direction in the surface region, and for example, it may be a gradient profile in which the concentration of the additive element gradually decreases from the surface toward the depth direction. It may also be a profile in which the concentration of the additive element increases once and then decreases from the surface toward the depth direction, or it may be a profile in which the concentration of the additive element in the depth direction of the surface region is almost uniform and the concentration of the additive element suddenly decreases on the way to the center.

[0062] Here, as described above, in addition to the above-mentioned additive elements, Ni element is also present in the surface region, and when y>0 or z>0 in the general formula (1), Mn element or Co element is also present. This means that the above-mentioned additive elements are present by penetrating (doping) into the surface region of the lithium-containing composite oxide having the composition represented by the general formula (1). In other words, the positive electrode active material according to this embodiment means that the surface of the lithium-containing composite oxide is not simply coated with a material containing the additive elements. There is no particular restriction on the concentration (abundance) of Ni element in the surface region, but the concentration of Ni element is preferably less than 10 mol%, more preferably 2 to 7 mol%, as a molar percentage with respect to all elements in the surface region. There is also no particular restriction on the value of the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface region, but from the viewpoint of further exerting the action and effect of the present invention, it is preferably 20.0 or less, more preferably 2.9 to 20.0.

[0063] The positive electrode active material used in the secondary battery according to this embodiment is a granular material of the lithium-containing composite oxide having the above-mentioned configuration. Here, the lithium-containing composite oxide according to this embodiment may be in the form of monodispersed primary particles, or in the form of secondary particles formed by aggregation of primary particles. However, from the viewpoint of further exerting the action and effect of the present invention, the lithium-containing composite oxide according to this embodiment is preferably in the form of primary particles. For the same reason, the average particle size of the lithium-containing composite oxide particles according to this embodiment is preferably 10 μm or less, more preferably 3.6 to 6.3 μm, as the 50% cumulative diameter (D50) converted into volume in the particle size distribution obtained by the laser diffraction scattering method.

[0064] Here, the method for producing the positive electrode active material (lithium-containing composite oxide) according to the present embodiment having the above-mentioned configuration is not particularly limited, and conventionally known knowledge can be appropriately referred to. Such a positive electrode active material (lithium-containing composite oxide) can be produced, for example, by the production method disclosed in JP 2020-35693 A or a method appropriately modified therefrom.

[0065] Here, the manufacturing method of the positive electrode active material (lithium-containing composite oxide) disclosed in the publication will be briefly described. In this manufacturing method, first, a transition metal raw material aqueous solution containing one or more transition metal compounds and an aqueous solution for nucleation containing an ammonium ion donor are supplied to a crystallization reaction tank while controlling the pH, ammonium ion concentration, and oxygen concentration in the atmosphere to a predetermined value, and nuclei are generated (nucleation step). Next, the nuclei generated in the nucleation step are grown as particles (particle growth step). This results in a transition metal composite hydroxide, which is a raw material for synthesizing the lithium-containing composite oxide. Next, the transition metal composite hydroxide obtained above is heat-treated (heat treatment step). Next, the heat-treated transition metal composite hydroxide and a lithium compound are mixed to form a lithium mixture (mixing step). After that, the mixture formed in the mixing step is fired (fired step). This results in a lithium-containing composite oxide. Here, in the manufacturing method disclosed in the publication, as a method for making an additive element different from that of the present invention exist on the surface layer of a transition metal composite hydroxide, a method is disclosed in which the transition metal composite hydroxide obtained above is slurried with an aqueous solution containing the additive element (or an alkoxide solution of the additive element), and the aqueous solution is further added while controlling the pH to a predetermined value, and the additive element is precipitated on the surface of the composite hydroxide by a crystallization reaction, and a method is disclosed in which an aqueous solution or slurry containing the additive element is sprayed onto the transition metal composite hydroxide obtained above and dried. Furthermore, a method is also disclosed in which a slurry in which a transition metal composite hydroxide and a salt containing an additive element are suspended is spray-dried, and a method is also disclosed in which a transition metal composite hydroxide and a salt containing an additive element are mixed by a solid phase method. In manufacturing the positive electrode active material (lithium-containing composite oxide) according to this embodiment, a similar method can be adopted using the additive element (B, P, S, Si) according to the present invention instead of the additive element disclosed in the publication.

[0066] Although the positive electrode active material according to the present embodiment is a so-called high nickel positive electrode active material, it has the above-mentioned composition of the surface region, and therefore can sufficiently improve the initial discharge capacity and cycle durability of a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus. The mechanism by which such an effect is achieved by the configuration of the present invention is not completely clear, but the following mechanism is presumed. That is, in the conventionally known high nickel positive electrode active material having a composition represented by the above-mentioned general formula (1), the concentration of Ni element is high in the surface region as well as in the center, and Ni atoms and oxygen atoms form metal-oxygen (Ni-O) bonds in the surface region. This metal-oxygen bond is unstable during charging, unlike a covalent bond, and is cleaved as the charging reaction progresses. On the other hand, a sulfide solid electrolyte containing sulfur and phosphorus is prone to an oxidation (bonding with oxygen) reaction when in contact with a positive electrode active material at a high potential (≧3V (vs. lithium)), and the generation of active oxygen atoms due to the cleavage of the metal-oxygen bond in the above-mentioned positive electrode active material accelerates the progress of this oxidation reaction.

[0067] In contrast, in the positive electrode active material according to the present embodiment, the concentrations of Ni and O elements in the composition of the surface region are relatively decreased by adding the additive elements to the composition of the central portion. As a result, active oxygen atoms that promote the oxidation reaction caused by the contact of the above-mentioned specific sulfide solid electrolyte with the high potential positive electrode active material are less likely to be generated. In addition, in the surface region, the above-mentioned additive elements (B, P, S, Si) are electrochemically stable because they are covalently bonded to O atoms, which also acts in the direction of suppressing the generation of active oxygen atoms. As a result, it is considered that the progress of the oxidation reaction of the sulfide solid electrolyte accompanying the progress of the charging reaction is prevented, and the effect of the present invention, that is, the improvement of the initial discharge capacity and the cycle durability, is achieved. Here, among the additive elements, from the viewpoint of further expressing the effect of the present invention, it is preferable that B (boron) is present in the surface region as the additive element. This is because the atomic radius of B (boron) is smaller than the other additive elements (P, S, Si), and is the additive element present in the surface region that is least likely to inhibit the absorption and release of lithium ions in the lithium-containing composite oxide. In other words, by using B (boron) as the additive element, in addition to the effects of the present invention, the effect of improving the output characteristics due to the reduction in battery resistance (reaction resistance) can be obtained.

[0068] According to the study by the present inventors, it has been found that the effect of the present invention cannot be achieved even by the technique described in the above-mentioned Patent Document 1 (International Publication No. WO 2013 / 022034). This is presumably due to the influence of the expansion and contraction of the active material accompanying charging and discharging, and the peeling off of the reaction suppression layer due to the application of shear force during kneading in the slurry preparation process. In addition, there is a fundamental problem that coating with a layer containing a lithium-containing oxide acts in the direction of increasing resistance to the conduction of lithium ions and electrons. In addition, there is also a problem that the manufacturing cost increases because a process of separately providing the reaction suppression layer is required.

[0069] In some cases, a positive electrode active material other than the lithium-containing composite oxide may be used in combination. However, the content ratio of the above-mentioned predetermined lithium-containing composite oxide in the total amount of the positive electrode active material (100 mass%) is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, still more preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass%.

[0070] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 55 to 95 mass % from the viewpoint of preventing a decrease in the energy density of the secondary battery. The positive electrode active material layer may further contain a conductive assistant and / or a binder, and specific and preferred forms thereof may be similarly adopted to those described in the section on the negative electrode active material layer above.

[0071] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 27 and the negative electrode current collector plate 25 may be made of the same material or different materials.

[0072] [Positive and negative leads] Although not shown, the current collectors (11, 12) and the current collector plates (25, 27) may be electrically connected via positive and negative electrode leads. The materials used in known lithium ion secondary batteries may be used as the materials for the positive and negative electrode leads. The parts removed from the exterior are preferably covered with a heat-resistant insulating heat shrink tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing a current leak and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0073] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.

[0074] The stacked battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.

[0075] While one embodiment of a lithium ion secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and may be modified as appropriate based on the claims.

[0076] For example, the type of battery to which the lithium ion secondary battery according to the present invention can be applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.

[0077] Fig. 3 is a cross-sectional view showing a bipolar lithium ion secondary battery (hereinafter, simply referred to as a "bipolar battery") which is one embodiment of the lithium ion secondary battery according to the present invention. The bipolar battery 10b shown in Fig. 3 has a structure in which a substantially rectangular power generating element 21, where the actual charge and discharge reaction proceeds, is sealed inside a laminate film 29 which is a battery exterior body.

[0078] As shown in FIG. 3, the power generating element 21 of the bipolar battery 10b of this embodiment has a plurality of bipolar electrodes 23, each having a positive electrode active material layer 15 electrically coupled to one surface of a current collector 11 and a negative electrode active material layer 13 electrically coupled to the other surface of the current collector 11. The bipolar electrodes 23 are stacked with a solid electrolyte layer 17 interposed therebetween to form the power generating element 21. The solid electrolyte layer 17 has a configuration in which a solid electrolyte is formed into a layer shape. As shown in FIG. 3, the solid electrolyte layer 17 is sandwiched and disposed between the positive electrode active material layer 15 of one bipolar electrode 23 and the negative electrode active material layer 13 of another bipolar electrode 23 adjacent to the one bipolar electrode 23.

[0079] Adjacent positive electrode active material layer 15, solid electrolyte layer 17, and negative electrode active material layer 13 constitute one unit cell layer 19. Therefore, it can be said that bipolar battery 10b has a configuration in which unit cell layers 19 are stacked. Note that positive electrode active material layer 15 is formed on only one surface of outermost current collector 11a on the positive electrode side, which is located in the outermost layer of power generating element 21. Also, negative electrode active material layer 13 is formed on only one surface of outermost current collector 11b on the negative electrode side, which is located in the outermost layer of power generating element 21.

[0080] 3, a positive electrode current collector (positive electrode tab) 25 is disposed adjacent to the outermost current collector 11a on the positive electrode side, and extends out from the laminate film 29 that is the battery exterior body. Meanwhile, a negative electrode current collector (negative electrode tab) 27 is disposed adjacent to the outermost current collector 11b on the negative electrode side, and similarly extends out from the laminate film 29.

[0081] The number of times that the cell layers 19 are stacked is adjusted according to the desired voltage. In bipolar battery 10b, the number of times that the cell layers 19 are stacked may be reduced if sufficient output can be ensured even if the thickness of the battery is made as thin as possible. In bipolar battery 10b as well, it is preferable to have a structure in which power generating element 21 is vacuum-encapsulated in laminate film 29, which is the battery exterior body, and positive electrode current collector 27 and negative electrode current collector 25 are exposed to the outside of laminate film 29 in order to prevent external impacts and environmental deterioration during use.

[0082] In addition, the secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur.

[0083] The liquid electrolyte (electrolytic solution) that can be used has a form in which a lithium salt is dissolved in an organic solvent. Examples of the organic solvent that can be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), propylene carbonate (PC), butylene carbonate (BC), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). Among these, from the viewpoint of further improving the rapid charging characteristics and output characteristics, the organic solvent is preferably a chain carbonate, more preferably at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and more preferably selected from ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).

[0084] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Among these, the lithium salt is preferably Li(FSO2)2N (LiFSI) from the viewpoints of battery output and charge / discharge cycle characteristics.

[0085] The liquid electrolyte (electrolytic solution) may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.

[0086] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.

[0087] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. Then, a large capacity, high output assembled battery (battery module, battery pack, etc.) suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large capacity assembled battery can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.

[0088] [vehicle] The battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a battery with excellent long-term reliability and long life can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if the battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for an uninterruptible power supply device or the like. EXAMPLES

[0089] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.

[0090] Example of test cell preparation [Comparative Example 1] As the positive electrode active material, LiNi 0.8 Mn 0.1 Co 0.1A lithium-containing composite oxide having a uniform composition of O2 and a form of secondary particles that are aggregates of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (secondary particles) was measured by a laser diffraction scattering method and found to be 11.5 μm. The elemental composition of the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportion of Ni to the total elements was 15 mol % and 57 mol %, respectively. The ratio of the concentration of O (oxygen) to the concentration of Ni in the surface region (O / Ni), calculated from these values, was 3.8. In addition, during the XPS measurement, a correction was made to shift the C1s peak top to 284.6 [eV] as a charging correction.

[0091] On the other hand, a lithium ion conductive sulfide solid electrolyte containing sulfur and phosphorus, LPS (Li2S-P2S5 (mixture ratio 80:20 (mol%))) was prepared as a solid electrolyte. In addition, acetylene black was prepared as a conductive additive.

[0092] 60 parts by mass of the positive electrode active material prepared above, 6 parts by mass of the conductive assistant, and 34 parts by mass of the sulfide solid electrolyte were weighed out and mixed using a table mill to prepare a positive electrode mixture.

[0093] Next, LPS (Li2S-P2S5 (mixture ratio 80:20 (mol%))), a sulfide solid electrolyte similar to that described above, was placed in a jig (McCool tube) and compacted at a molding pressure of 400 MPa to produce a solid electrolyte layer (disk shape with a diameter of 10 mm and a thickness of 600 μm).

[0094] Next, the positive electrode mixture prepared above was placed on one side of the solid electrolyte layer produced above, and powder-molded at a molding pressure of 200 [MPa] to produce a positive electrode active material layer (disk shape with a diameter of 10 mm and a thickness of 70 μm).

[0095] Then, a Li-In electrode consisting of a laminate of lithium metal foil (thickness 100 μm) and indium metal foil (thickness 100 μm) was prepared as a negative electrode. This Li-In electrode was then placed on the other side of the solid electrolyte layer prepared above, with the indium metal foil facing the solid electrolyte layer. Next, the jig was fastened with a restraining pressure of 100 [MPa], and a lead for taking out current was connected to each electrode to prepare a test cell for this comparative example.

[0096] [Comparative Example 2] As the positive electrode active material, LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2 and a form of secondary particles that are aggregates of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (secondary particles) was measured by a laser diffraction scattering method and found to be 10.5 μm. The elemental composition of the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS) and found to be 10 mol % Ni and 56 mol % O, as proportions of all elements. The ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface region, calculated from these values, was 5.6.

[0097] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0098] [Comparative Example 3] As the positive electrode active material, LiNi 0.8 Mn 0.1 Co 0.1A lithium-containing composite oxide having a uniform composition of O2 and a form of secondary particles that are aggregates of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (secondary particles) was measured by a laser diffraction scattering method and found to be 10.2 μm. The elemental composition of the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS) and found to be 12 mol % Ni and 55 mol % O, as proportions of all elements. The ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface region, calculated from these values, was 4.6.

[0099] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0100] [Comparative Example 4] As the positive electrode active material, LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2 and a form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 4.5 μm. The elemental composition of the surface region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS) and found to be 13 mol % Ni and 60 mol % O, as proportions of all elements. The ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface region, calculated from these values, was 4.6.

[0101] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0102] [Example 1] The positive electrode active material is LiNi 0.8 Mn 0.1 Co0.1 A lithium-containing composite oxide having a uniform composition of O2, containing B (boron) in the surface layer region, and having the form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 3.6 μm. In addition, the elemental composition of the surface layer region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportions of all elements were Ni 5 mol %, O 36 mol %, and B 24 mol %. In addition, the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface layer region calculated from these values ​​was 7.2.

[0103] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0104] [Example 2] The positive electrode active material is LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2, containing B (boron) in the surface layer region, and having the form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 3.6 μm. In addition, the elemental composition of the surface layer region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportions of all elements were Ni 7 mol %, O 20 mol %, and B 30 mol %. In addition, the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface layer region calculated from these values ​​was 2.9.

[0105] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0106] [Example 3] The positive electrode active material is LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2, containing B (boron) in the surface layer region, and having the form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 4.3 μm. In addition, the elemental composition of the surface layer region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportions of all elements were Ni 2 mol%, O 40 mol%, and B 17 mol%. In addition, the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface layer region calculated from these values ​​was 20.0.

[0107] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0108] [Example 4] The positive electrode active material is LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2, containing B (boron) in the surface layer region, and having the form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 4.6 μm. In addition, the elemental composition of the surface layer region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportions of all elements were 3 mol% Ni, 40 mol% O, and 17 mol% B. In addition, the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface layer region calculated from these values ​​was 13.3.

[0109] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0110] [Example 5] The positive electrode active material is LiNi 0.8 Mn 0.1 Co 0.1 A lithium-containing composite oxide having a uniform composition of O2, containing B (boron) in the surface layer region, and having the form of primary particles was prepared. The average particle diameter (D50) of this lithium-containing composite oxide (primary particles) was measured by a laser diffraction scattering method and found to be 3.6 μm. In addition, the elemental composition of the surface layer region within a depth of 100 nm from the surface of the lithium-containing composite oxide particles prepared above was measured by X-ray photoelectron spectroscopy (XPS), and the proportions of all elements were Ni 3 mol %, O 57 mol %, and B 17 mol %. In addition, the ratio (O / Ni) of the concentration of O (oxygen) to the concentration of Ni in the surface layer region calculated from these values ​​was 19.0.

[0111] A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that the lithium-containing composite oxide prepared above was used as the positive electrode active material.

[0112] <Test cell evaluation example> For the test cells prepared in each of the above Comparative Examples and Examples, the discharge capacity per mass of the positive electrode active material was measured by the following method.

[0113] First, the test cell was sandwiched between two 5mm-thick stainless steel plates, and the clamping pressure was 1000kgf / cm 2 The material was pressed using a flat plate press via a hydraulic jack so that the pressure was as follows:

[0114] After 1 hour had passed after the pressure application, the test cell was placed inside a thermostatic chamber set at 25°C, and connected to a charge / discharge device to perform a charge / discharge test, and the charge / discharge capacity was measured. At this time, in the charging process, a current equivalent to 0.05C was applied, and CC-CV charging was performed with an upper limit voltage of 3.6V (vs. Li-In negative electrode). In addition, this charging process was terminated when the current value decreased to a value equivalent to 0.01C or when 40 hours had passed since the start of charging. After the charging process was terminated, the cell was left for 1 hour and then discharged. In the discharging process, CC discharging was performed with a current value equivalent to 0.05C and a lower limit voltage of 1.9V (vs. Li-In negative electrode). Then, the capacity (discharge capacity) was measured during the discharging process, and standardized by the mass of the positive electrode active material used in each test cell, and the discharge capacity per mass of the active material was calculated as the initial discharge capacity. The results are shown in Table 1 below.

[0115] In addition, the above-mentioned charge / discharge process was counted as one cycle, and a total of 50 charge / discharge cycles were performed. In this case, a rest period of one hour was provided between the charge / discharge processes to leave the test cell standing. Then, as an index of cycle durability, the percentage of the discharge capacity at the 50th cycle relative to the initial discharge capacity was calculated as the capacity retention rate after 50 cycles. The results are shown in Table 1 below. Note that, since the initial discharge capacity of Comparative Example 1 was an extremely small value, the capacity retention rate could not be evaluated.

[0116] [Table 1]

[0117] From the results shown in Table 1, it can be seen that by using a positive electrode active material made of a lithium-containing composite oxide having a specified additive element in the surface layer region, it is possible to sufficiently improve the initial capacity and cycle durability of a secondary battery using a sulfide solid electrolyte containing sulfur and phosphorus and a high-nickel positive electrode active material. [Explanation of symbols]

[0118] 10a Stacked battery, 10b Bipolar battery, 11 current collector, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.

Claims

1. The composition of the central portion is the following chemical formula (1): Li 1+q Ni x Co y Mn z M p O 2 (1) In the formula, −0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. A positive electrode including a positive electrode active material layer containing a positive electrode active material made of a lithium-containing composite oxide represented by the formula: a solid electrolyte layer containing a sulfide solid electrolyte containing sulfur and phosphorus; a negative electrode including a negative electrode active material layer containing a negative electrode active material; The power generating element is formed by stacking the above in this order. a secondary battery in which one or more additive elements selected from the group consisting of B, S and Si are present at a molar concentration higher than that of Ni in a surface layer region within a depth of 100 nm from the surface of a particle of the lithium-containing composite oxide, and Ni is present in the surface layer region.

2. The composition of the central portion is the following chemical formula (1): Li 1+q Ni x Co y Mnz M p O 2 (1) In the formula, −0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. A positive electrode including a positive electrode active material layer containing a positive electrode active material made of a lithium-containing composite oxide represented by the formula: a solid electrolyte layer containing a sulfide solid electrolyte containing sulfur and phosphorus; a negative electrode including a negative electrode active material layer containing a negative electrode active material; The power generating element is formed by stacking the above in this order. The secondary battery comprises a surface layer region within a depth of 100 nm from the surface of the particle of the lithium-containing composite oxide, in which phosphorus (P) as an additive element is present at a molar concentration of 17 to 30 mol %, which is higher than that of Ni, and Ni is present in the surface layer region.

3. 3. The secondary battery according to claim 1, wherein the amount of Ni present in the surface region is 2 to 7 mol %.

4. The secondary battery according to claim 1 , wherein the additional element comprises B.

5. 5. The secondary battery according to claim 1, wherein a ratio (O / Ni) of a concentration of O (oxygen) to a concentration of Ni in the surface region is 20.0 or less.

6. The secondary battery according to any one of claims 1 to 5, wherein the lithium-containing composite oxide is in the form of primary particles, and the average particle diameter (D50) of the lithium-containing composite oxide is 10 µm or less.

7. 7. The secondary battery according to claim 1, wherein the content of the positive electrode active material in the total amount (100 mass%) of the solid content of the positive electrode is 55 to 95 mass%.

8. The secondary battery according to any one of claims 1 to 7, wherein, in the general formula (1), 0.60≦x≦0.

90.

9. The secondary battery according to any one of claims 1 to 8, which is an all-solid-state lithium ion secondary battery.

10. The composition of the central portion is the following chemical formula (1): Li 1+q Ni x Co y Mn z M p O 2 (1) In the formula, −0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. The lithium-containing composite oxide is represented by a surface layer region within a depth of 100 nm from the surface of a particle of the lithium-containing composite oxide, in which one or more additive elements selected from the group consisting of B, S and Si are present at a molar concentration higher than that of Ni, and Ni is present in the surface layer region.

11. The composition of the central portion is the following chemical formula (1): Li 1+q Ni x Co y Mnz M p O 2 (1) In the formula, −0.02≦q≦0.20, x+y+z+p=1, 0.5≦x≦1.0, 0≦y≦0.5, 0≦z≦0.5, 0≦p≦0.1, and M is one or more elements selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. The lithium-containing composite oxide is represented by In the positive electrode active material for a secondary battery, in a surface layer region within a depth of 100 nm from the surface of a particle of the lithium-containing composite oxide, phosphorus (P) as an additive element is present at a molar concentration of 17 to 30 mol %, which is higher than that of Ni, and Ni is present in the surface layer region.

12. 12. The positive electrode active material for a secondary battery according to claim 10, wherein the amount of Ni present in the surface layer region is 2 to 7 mol %.

Citation Information

Patent Citations

  • Method of manufacturing positive electrode active material for solid battery

    JP2016170942A

  • Positive electrode for lithium secondary battery, lithium secondary battery, and method for manufacturing positive electrode for lithium ion secondary battery

    JP2017033839A

  • Positive electrode active material for lithium secondary battery, method for producing the same, positive electrode for lithium secondary battery containing the same, and lithium secondary battery

    JP2020525991A

  • Composite positive electrode active substance, all-solid-state cell, and method for producing composite positive electrode active substance

    WO2013022034A1

  • Positive electrode active material, positive electrode material, positive electrode, and non-aqueous electrolyte secondary battery

    WO2014133064A1